Incorporating location and inventory decisions into a supply chain design problem with uncertain demands and lead times. (April 2017) - Diabat, Ali; Dehghani, Ehsan; Jabbarzadeh, Armin
Highlights: We present a joint location-inventory model for the network design. The uncertain natures of demands and replenishment lead times are incorporated into the model utilizing a queuing approach. A hybrid solution algorithm based on simulated annealing and direct search method is adopted. Abstract: This paper presents a joint location-inventory model for the network design of a supply chain with multiple Distribution Centers (DCs) and retailers. The developed model determines the number and location of DCs, the assignment of retailers to DCs, and the size and timing of orders for each DC. The uncertain natures of demands and replenishment lead times are incorporated into the model utilizing a queuing approach. To solve the presented model for large size problems, a hybrid solution algorithm based on simulated annealing and direct search method is adopted. The comparative analysis of the numerical results provides important modelling insights. Particularly, we demonstrate numerically that the cost savings obtained from the queuing approach can be significant.